BIMBINGAN PSIKO–RELIGIOUS BAGI PASIEN RAWAT INAP RUMAH SAKIT UMUM DAERAH DI JAWA TENGAH (Formulasi Ideal Layanan Bimbingan dan Konseling Islam) - Komarudin Komarudin (At-Taqaddum, 2012)
Model guidance and counseling for patients in hospital is still limited to the provision of services doa, religious guidances, edvice to be patients and put their trus to Allah , as well as assistance for patients who have al-death–death bed/dying (sakaratul maut). In fact, on the other hand the condition of patients in need of guidance is very diverse, thus requiring the application of methods, approaches, and models of different services. There for the implementation of guidance and counseling services for patients in hospital need to be formulated in the form of appropriate service based on the needs and sircumstances specified by the patients themselves. There are patients who only need guidance, but there are patients who typically require intensive treatment through the provision of counseling services. That’s why, the model seems to services for patients in theory should be categorized into two models, namely models of counseling services, which cater to regular patients, and the model of counseling services with special needs.This paper aims to describe the implementation of models of Islamic guidance and counseling services for patients in general hospital in central Java, and show that the service ideal formulation should be applied in order to meet/cater/fulfill the patients needs and specification. The ideal formulation of services for patients should be categorized into three models, namely models of guidance services, counseling services model, and model a combination of both. In addition, each service must be accompanied by the good and right recording process and all records documenting the results of administrative services.